The impact of social media on men's psychological reactance and transforming perceptions of gender discrimination - Su, Charlize Xiu Yen (Nanyang Technological University, 2024)
This study examines the influence of Digital Feminist Activism (DFA) on attitudes towards gender equality and reactance among young men in Singapore. DFA, characterised by its engagement in challenging conversations about gender inequities and sexism on social media, has primarily been explored from the perspective of women’s participation, emphasising its role in raising awareness and fostering connectivity. However, this research fills a gap by investigating men’s perceptions within the DFA context. Drawing on theories of social identity theory and empathy, the study explores how factors such as gender identity, the gender of DFA post writers, and levels of empathy impact sexist attitudes and psychological reactance. Through online surveys, data were collected from a sample of 54 young men aged 18 to 35 years old, incorporating measures of gender traits, empathy, sexist attitudes and reactance to DFA messages. The results reveal mixed findings, with significant effects observed for gender identity in reducing sexist attitudes and partial support for reducing reactance. Individual differences in empathy also had a moderating effect on the relationship between gender identity and reactance, as well as gender of the writer and reactance. These findings underscore the complex interplay between psychological variables and digital activism in shaping attitudes towards gender equality among young men, highlighting the need for further research and nuanced interventions to promote gender equity in contemporary society.